How incumbents respond to competition from innovative disruptors in the sharing economy—The impact of Airbnb on hotel performance - Chang, Hung‐Hao; Sokol, D. Daniel (Strategic Management Journal, 2022)
Abstract Research Summary This article investigates the impacts of Airbnb on hotel demand and the price and nonprice response strategies of incumbent hotels to Airbnb. We constructed a unique dataset of tourist hotels and Airbnb listings before and after the entry of Airbnb in Taiwan. We found that the entry of Airbnb makes the hotel industry more heterogeneous. Low quality hotels compete on price with Airbnb after Airbnb's entry. In contrast, prices and the investment in service quality increase for high quality hotels. These findings suggest that high quality hotels reposition themselves in the higher end of the lodging market as a response strategy to the entry of Airbnb. Managerial Summary Incumbent hotels can use a number of strategies to respond to Airbnb's entry. Using a unique dataset of Taiwanese data from before and after Airbnb's entry, we found that hotels' responses differ across the value chain. Low quality hotels compete on price with Airbnb after Airbnb's entry. In contrast, prices and the investment in service quality increase for high quality hotels. The increase of investment in service quality allows high quality hotels to reposition themselves in the higher end of the lodging market.